Coupled discrete element modeling of fluid injection into dense granular media. Issue 6 (27th June 2013) - Zhang, Fengshou; Damjanac, Branko; Huang, Haiying
Abstract : [1] The coupled displacement process of fluid injection into a dense granular medium is investigated numerically using a discrete element method (DEM) code P F C 2 D ® coupled with a pore network fluid flow scheme. How a dense granular medium behaves in response to fluid injection is a subject of fundamental and applied research interests to better understand subsurface processes such as fluid or gas migration and formation of intrusive features as well as engineering applications such as hydraulic fracturing and geological storage in unconsolidated formations. The numerical analysis is performed with DEM executing the mechanical calculation and the network model solving the Hagen‐Poiseuille equation between the pore spaces enclosed by chains of particles and contacts. Hydromechanical coupling is realized by data exchanging at predetermined time steps. The numerical results show that increase in the injection rate and the invading fluid viscosity and decrease in the modulus and permeability of the medium result in fluid flow behaviors displaying a transition from infiltration‐governed to infiltration‐limited and the granular medium responses evolving from that of a rigid porous medium to localized failure leading to the development of preferential paths. The transition in the fluid flow and granular medium behaviors is governed by the ratio between the characteristic times associated with fluid injection and hydromechanical coupling. The peak pressures at large injection rates when fluid leakoff is limited compare well with those from the injection experiments in triaxial cells in the literature. The numerical analysis also reveals intriguing tip kinematics field for the growth of a fluid channel, which may shed light on the occurrence of the apical inverted‐conical features in sandstone and magma intrusion in unconsolidated formations. Key Points: Fluid injection into dense granular media modeled numerically Numerically produced displacement patterns consistent with experiments Material parameters scaling verified numerically